Floods - Vinet, Freddy (London Elsevier, 2017)
The management of flood risk seems to be facing a daunting paradox. Despite increasingly effective risk knowledge tools and the efforts of international institutions to place risk reduction at the top of the agenda, the cost of disasters continues to increase. It is also increasingly difficult to avoid the urbanization or development of potential flood zones. The fundamental issue involves determining the conditions necessary for efficient prevention by focusing on adaptability to risk, which implies coping with the risk of flooding rather than directly fighting against it or simply ignoring it. This second volume of the Floods series of books explores existing policies and tools which mitigate the impact of flooding: the construction of protective structures, the reduction of vulnerability, land use planning, the improvement of crisis management, etc. The closing chapters focus on the question of adaptation through post-flood reconstruction, integrating disaster risk reduction measures, e.g. through resilient urbanism.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Flood control; Flood damage prevention; Floods -- Risk management; Electronic books